Artificial Intelligence (AI) in the Financial Sector—Potential and Public Strategies - Bredt, Stephan (Frontiers in Artificial Intelligence, 2019)
AI is providing a significant basis for future technological innovation. The financial sector will be transformed by AI, offering the opportunity for better and more tailor made services, cost reduction and the development of new business models. The Federal and the Hessen government recently published roadmaps for the further development of AI in Germany and Hessen respectively. The federal government will invest 3 Bill. Euro over the next 5 years in a variety of research and business sectors whereas the State of Hessen will set up a new AI oriented institute of applied research and business development and spend one billion Euro over the next five years on digitalisation development. The public strategies for building AI Hubs are still extremely diverse. However, the focus is on stronger application of research results in business activities, on increasing networks and ecosystems and predominantly on building on existing centers of excellence. Especiallly the Frankfurt Rhein Main Region, already a strong hub for fintech, cyber security and AI will benefit from these programs. The financial center Frankfurt offers a vivid and fast growing tech and start up community a well as an academic and data infrastructure unprecedented in Europe: the largest data and cloud service hub in continental Europe, the worlds largest internet knot, universities, research institutes with global quality research in AI, companies and consultancies specialised in AI and neighbouring areas such as fintech and cyber security.